BMC Research Notes - Brod, Samuel; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Research Notes is an open access journal publishing peer-reviewed contributions from across all scientific and clinical disciplines, including intriguing initial observations, updates to previous work and established methods, valid negative results, and scientific data sets and descriptions. We are committed to making it easier to find, cite and share your short reports by providing an inclusive forum for valuable data and research observations. The journal welcomes manuscripts that fall into the into the following research areas Health sciences and medicine Biology and life sciences Physical sciences and engineering Scientific community: Bioethics Data publishing Education (medical and scientific) Research methodology Metascience and more.
Keywords: Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Public health; Life sciences; Biomedical Research; Public Health; Life Sciences